Implementation of image file security using the advanced encryption standard method - Ali Ikhwan; Rafikha Aliana A. Raof; Phaklen Ehkan; Yasmin Yacob; Nuri Aslami (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The application of technology in this era has entered digitalization and is modern. Therefore, we are already in an era of advanced and rapid technological development. It has become a human need to exchange information in every activity. Documents that contain information that is frequently sought or used. The document's use also includes essential information. Document security is undoubtedly a significant factor in prioritizing important information in a document to prevent unauthorized people from misusing the document's vital information. Cryptography is a method of overcoming document security issues so that third parties cannot read the information or messages contained within the document. The 128-bit advanced encryption standard (AES) algorithm is one of the algorithms included in the cryptography technique. Additionally, it can be combined with operation modes such as electronic codebook (ECB) and cipher block chaining (CBC) to create an application that can generate random codes to improve the security of the data contained in the document.